Sosialisasi Strategi Masjid Dalam Pemberdayaan Ekonomi Umat - zulkifli, Zulkifli; Saputra, Hendra Eka; Hermanto, Budi (UIR Press, 2025)
Mosques as places of worship today have changed in terms of function. In the time of the Prophet and his companions, mosques were used as places of worship as the main function and as economic activities for the people. The current era makes the function of mosques only as places of worship, therefore socialization was carried out regarding the strategy of mosques in empowering the people's economy. The activity began with the formation of a small team to make a work program plan and continued with a request for permission for socialization to the head of the RT and the head of the local Mosque Management Council (DKM). After obtaining permission, the team began carrying out activities in accordance with the previously determined work program plan. The results of this socialization received appreciation and additional insight and there were people who had made purchases even though the transactions were not in the mosque, but were carried out by the community from goods/services that were available from the community around the mosque so that empowerment of businesses in the radius of the mosque became a priority who wanted to shop according to the needs of the congregation.